Identifikasi dalam Penetapan Staf Dosen dan Karyawan Berprestasi dengan Menggunakan Metode SMART - Azizah, Nur; Nurcahyo, Gunadi Widi (Rektorat Universitas Putra Indonesia YPTK Padang, 2021)
STMIK Indonesia Padang annually selects the best lecturers and employees to give appreciation for the performance of lecturers and employees. Lecturers and employees who take the assessment to appreciate the Performance Appraisal must meet the requirements and participate in the assessment process. The purpose of this research is to identify in determining the staff of lecturers and staff with achievement who are shorter in terms of calculations and also in accordance with the criteria. The sample in this study consisted of 4 lecturer data and 3 employee data taken randomly from 36 lecturer data and 26 employee data sourced from LP3M STMIK Indonesia Padang. Based on the analysis of lecturer and employee data, several criteria were obtained for processing these criteria, namely for lecturers the suitability of teaching materials with RPS (K) (Q1) teaching materials (Q2), teaching time (Q3), research (Q4) and GPA (Q5). ) then for employees, namely attendance (R1), performance (R2) and loyalty (R3). The method in this research is SMART (Simple Multi - Attribute Rating Technique) because this method is able to solve problems with multi-criteria. The results of the data testing obtained were Lecturers with achievements, namely DHD lecturers with a value of 0.8521 and outstanding employees, namely ARD employees with a value of 0.9998. The results of this study are expected to provide solutions for the identification of outstanding lecturers and staff at STMIK Indonesia Padang based on predetermined criteria.